The Selenium Yeast vs Selenium Methionine on Cell Viability, Selenoprotein Profile and Redox Status via JNK/ P38 Pathway in Porcine Mammary Epithelial Cells - Wu, Caichi; Cui, Chang; Zheng, Xiaoyu; Wang, Jun; Ma, Ziwei; Zhu, Pengwei; Lin, Gang; Zhang, Shihai; Guan, Wutai; Chen, Fang (Frontiers in Veterinary Science, 2022)
Comprehensive studies have been conducted to compare the effect of organic and inorganic selenium previously, but there is still limiting knowledge about the difference between organic selenium (Se) from varied sources despite the widely use of organic Se in both animal and human being nutrient additives. In present study, we systemically compared the effect of two different types of organic Se including selenium yeast (SeY) and selenium methionine (Sel-Met) on cell viability, selenoprotein transcriptome, and antioxidant status in porcine mammary epithelial cells (PMECs) and the results indicated that appropriate addition of SeY and Sel-Met both significantly promoted cell viability and up-regulated the mRNA expression of most selenopreoteins including DIOs, GPXs, and TrxRs family et al (P < 0.05). Besides, two different sources of Se supplementation both greatly improved redox status with higher levels of T-AOC, SOD, and CAT (P < 0.05), while less content of MDA (P < 0.05), and reduced protein expression of cleaved-caspase-3 (P < 0.05) to mitigate cell apoptosis. Furthermore, the key proteins related to p38/JNK pathway including p38, p-p38, JNK, and p-JNK were apparently reduced in the groups with both of SeY and Sel-Met (P < 0.05). Interestingly we found that the changes induced by SeY supplementation in cell viability, selenoprotein transcriptome, antioxidative capacity and anti-apoptosis were comprehensively greater compared with same levels addition of Sel-Met in PEMCs (P < 0.05). In conclusion, both SeY and Sel-Met promoted cell viability and attenuated cell apoptosis by regulating the selenoprotein expression and antioxidative capacity via p38/JNK signaling pathway in PMEC, but SeY has more efficient benefit than that of Sel-Met.